The Management of Urban Development for the Regional Economic Growth: the Example of Kazakhstan - Mukhametzhan, Svetlana O.; Junusbekova, Gulsara A.; Daueshov, Marat Ye. (Economy of Regions, 2020)
Considering the increasing imbalance in the economic development of urbanised territories of Kazakhstan, examining the impact of urbanisation on the economic growth of cities to ensure their innovative development is necessary. This study analyses trends and problems of the impact of urbanisation on urban development on the example of Kazakhstan. The article focuses on urban development and related processes that will open new opportunities for Kazakhstan to accelerate economic growth and improve living standards. The works of local researchers do not show the relationship between the levels of urban and economic development in different regions of the country and the impact of urbanisation on this process. To supplement previous studies, we used statistical and comparative analysis methods. Moreover, we compared the current state of urban development in Kazakhstan with the situation in other countries. The obtained empirical estimates confirm the correlation between the level of urbanisation of a country and its economic growth. Without a holistic approach to urban management, it is difficult to establish the directions, principles and development strategies for Kazakhstan’s cities and megacities to follow. Thus, we identified the main directions for economic growth of urbanised territories of Kazakhstan: proper control and management of urbanisation, flexible management, development of appropriate policies for different regions of the country, use of best practices in developing urban strategies. We recommend considering the analysis of urban management in the broader context, and not only as a task of implementing regional economic growth. For that purpose, it is necessary to create an integrated multi-level management system that provides feedback and preventive management, classifying the consequences of urban policy in the regions and the effects of achieving the country’s strategic development goals. Therefore, the Kazakh government should at least review its functions and responsibilities and look for solutions to achieve a tangible synergistic effect.